The Efforts of Koninklijke Paketvaart Maatschappij (KPM) in Maintaining the Existence of Its Shipping Network in Indonesia 1945–1958 - Navil Alfarisi Abbas; Ulul Azmi Muhammad; Ardhi Yudhistira (Swarnadwipa, 2026)
The purpose of this research is to find out what the Koninklijke Paketvaart Maatschappij (KPM) efforts were in maintaining the existence of the shipping network in Indonesia in 1945-1958. The method used in this study is the historical method with data collection techniques, namely library and documentation techniques, as well as qualitative data analysis techniques. . The results of this research are the  KPM's attempts to regain control of shipping in Indonesian territory with the efforts made as one of the Dutch shipping companies that were given monopoly rights, resulted in failure. The losses and the many rejections and efforts to nationalize Dutch companies, including KPM ownership, were the end of KPM's operations on Indonesian shipping routes